An investigation of the passive control of air pollution in the urban environment - Gallagher, John (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
Poor air quality is a universal problem in built-up environments and presents a continued threat to the health of urban populations. Vehicle emissions have been identified as the predominant source of urban air pollution. This research aims to investigate controls which engineer the natural air flow patterns in urban street canyons. The control of air pollutants between a vehicle source and human receptor is carried out through the introduction of passive controls, such as low boundary walls or parked cars, and reduces personal pollutant exposure by increasing dispersion at street level in an urban canyon. This thesis describes three investigations; two generic modelling studies and a real world case study, to determine the potential of these passive controls in urban street canyons. The computational fluid dynamic (CFD) software FLUENT was adopted to simulate these street canyons and evaluate the effects of passive controls on pollutant dispersion within an urban environment.
Keywords: Civil, Structural & Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin